PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PERAWAT RAWAT INAP PADA RUMAH SAKIT EKA HOSPITAL PEKANBARU - Agus Rianto; Alvi Furwanti; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted at Eka Hospital Pekanbaru which is located 6.5 Km Jl. Soekarno Hatta Riau - Pekanbaru. The purpose of this study was to determine the effect of transformational leadership on OCB nurse-patient at the Eka Hospital Pekanbaru, To determine the effect of organizational commitment on Organizational Citizenship Behavior nurse-patient at the Eka Hospital Pekanbaru and To determine the effect of transformational leadership and commitment OCB on organizational nurse on hospital inpatient Eka Hospital Pekanbaru. the study population was 55 nurses on hospital inpatient Eka Hospital Pekanbaru with accidental sampling models. Variable research is transformational leadership and organizational commitment as an independent variable and Organizational Citizenship Behavior as the dependent variable. Methods of data analysis using multiple linear regression analysis. The results of this study concluded that transformational leadership and organizational commitment partially and simultaneously have a significant influence on OCB inpatient nurse at the Eka Hospital Pekanbaru. Where is the most dominant factor affecting the OCB is a factor of transformational leadership. Research that has been conducted in accordance with the regression test (t test) and (f test) shows independent variables studied are variable transformational leadership and organizational commitment have a significant effect on the dependent variable Organizational Citizenship Behavior nurse.Keywords: Transformational Leadership, Organizational Commitment and OCB